Analisis Bibliometrik Model Regresi Spline untuk Pemetaan Tren dan Pengembangan Strategi Penelitian Menggunakan VOSviewer - Al Barra, Andre Fajry; Saputro, Dewi Retno Sari; Widiyaningsih, Purnami (Neolectura, 2024)
Bibliometric analysis is a quantitative method used to measure and analyze scientific literature. This technique involves the collection and analysis of publication data, such as journal articles, books, and conferences, to evaluate and understand patterns of scientific communication, research productivity, author collaboration, journal impact, and trends within a scientific field. Bibliometric analysis has a limitation in that it is challenging to visualize effectively, necessitating the use of software for proper visualization. Therefore, this article discusses bibliometric analysis on spline regression for trend mapping and strategy development using VOSviewer software. The research results show that the visualization of spline regression keywords with VOSviewer can help in understanding patterns of relationships between variables, research trends, and network structures in scientific literature. Based on the analysis results, bibliometric analysis on spline regression can be visualized in trend mapping, which can aid in planning further research strategies, including identifying collaboration opportunities and underexplored research areas.